Acute Pneumonia: Biological Rules and Laws require Attention and Respect. - Klepikov, I. (Journal of Respiratory Diseases, 2019)
A perspective argues that biological rules and host–pathogen dynamics deserve greater attention in pneumonia care. It integrates pathophysiology with clinical decision‑making.